A prospective study on impact of patient counselling on quality of life of patients with atopic dermatitis - R., Ranjeth; Vijayasenan, Resmi; S., Amritha M.; Wesley, I. John (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Atopic dermatitis is an acute, sub-acute or chronic relapsing skin disorder characterized by intense itching, pruritus and oozing. It adversely affects the routine activities of patients for which effective treatment is to be provided along with proper counselling. The aim of the current study was to evaluate the impact of patient counselling on quality of life (QoL). Methods: A prospective study was conducted in 108 patients recruited from the Department of Dermatology for a period of 6 months. A written informed consent was taken. Out of the 108 patients, 54 patients received tacrolimus and the remaining received corticosteroids. The collected data was analysed and presented. Data was collected by using a suitably designed proforma. Dermatology life quality index (DLQI) was used for assessing QoL. Patients were counselled regarding the disease, drugs and lifestyle modifications using patient information leaflet (PIL). Results: The current study found that patient counselling was effective for both the groups with a p value <0.05. The effect of disease in quality of life improved from severe to mild in both groups (prior to counselling QoL mean value of 2.93±0.61 shifted to 1.18±0.71 post counselling). In the tacrolimus group, QoL mean value of 2.81±0.61 shifted to 0.98±0.71 after counselling. In the corticosteroids group, a shift from a mean QoL value of 3.05±0.59 to a mean of 1.38±0.65 was observed post counselling. Conclusions: The provision of effective counselling was found to have a profound impact on improving patient’s quality of life. A transition from severe effects of the disease to milder effects of the disease on quality of life was observed.